SEN!, ISLAM, dan AMRI (Upaya Awal Pemahaman dan Penilaiannya) - Haikal, H. (Jurnal Cakrawala Pendidikan, 2005)
Simple understanding puts art in a corner in Islamic belief though Islamic teaching provides art with a full position. This shows in Amri's works in art. ;\. study hasbeen based on an intensive literature research which has been strengthened by the writer's strong interest in Islamic art. A good relationship with Prof. Dr. (H.C.) Amri Yahyahas to some extent provided the writer with an ability to conduct an in-depth interview with the artist. This article tries to present an early remark concerning the peculiarity ofeach community in understanding and promoting its own art. In dealing with monumental works ofart, one needs more than one single yardstick for evaluating and measuring them. The situation becomes more complicated ifthere are religious aspects on them. Nevertheless, this article tries to highlight monumental works ofart, especially Amri's, with the writer admitting many possible short-comings in it and its possibility ofprovoking others to present their own views and, therefore, inviting them to write about those views as best as they could so that all may come to the best conclusions or agreements so badly needed. Key words: Amri, Art, Islam, evaluation, and understanding.